Non-prompt surgery for patients with acute type A aortic dissection without pre-operative shock and malperfusion - Wu, Shye-Jao; Fan, Ya-Fen; Tsai, Yu-Chu; Sun, Shen; Chien, Chen-Yen; Li, Jiun-Yi (Frontiers in Cardiovascular Medicine, 2022)
Background During daily practice, there were some patients with acute type A aortic dissection (ATAAD) sought for medical attention several days after symptoms occurred and some other patients hesitated to receive aortic surgery after the diagnosis of ATAAD was made. This study aims to investigate the impact and the effectiveness of non-prompt aortic surgery (delayed diagnosis by patient or delayed surgery despite immediate diagnosis) on surgical outcomes. Methods: From November 2004 to June 2020, of more than 200 patients with ATAAD patients who underwent aortic surgery at our hospital, there were 30 patients without pre-operative shock and malperfusion who sought for medical attention with symptoms for several days or delayed aortic surgery several days later despite ATAAD was diagnosed. Of the 30 patients (median age 60.9, range 33.4 82.5 years) in the study group, there were 18 patients undergoing surgery when they arrived at our hospital (delayed diagnosis by patient) and 12 patients receiving surgery days later (delayed surgery despite immediate diagnosis). Patients with prompt surgery after symptom onset (control group) were selected from our database by propensity score matching. Results: The in-hospital mortality and was 3.3% for the study group and 6.7% for the control group (p=non-significant). The incidence of post-operative cerebral permanent neurological defect was 0% for the study group and 13.3% for the control group (p=0.112). There were 3 patients receiving aortic re-intervention or re-do aortic surgery during follow-up for the study group and 2 patients for the control group. Conclusion: Prompt surgery for ATAAD is usually a good choice if everything is well prepared. Besides, urgent but non-prompt aortic surgery could also provide acceptable surgical results for ATAAD patients without pre-operative shock and malperfusion who did not seek for medical attention or who could not make their minds to undergo surgery immediately after onset of symptoms. Hospitalization with intensive care is very important for pre-operative preparation and monitoring for the patients who decline prompt aortic surgery.